The feminist war on crime: the unexpected role of women's liberation in mass incarceration - Gruber, Aya (University of California Press, 2020)
The opening battle : fighting patriarchy with purity -- The enemy : from "the man" to bad men -- The battle plan : arrest is best -- The weapon : ideal victims -- The new front : date rape -- From the sexual cold war to the new sex panic -- Endless war?